2022
DOI: 10.3991/ijet.v17i11.29931
|View full text |Cite
|
Sign up to set email alerts
|

Developing Student Creative Problem-Solving Skills (CPSS) Using Online Digital Storytelling

Abstract: This study set out to research and evaluate the needs in developing creative problem-solving skills (CPSS) of undergraduate students through developing and evaluating a digital storytelling process using Padlet. The sampling process used simple random sampling to select 332 teachers from 83 schools in Bangkok. The data was collected using a needs assessment questionnaire, training course questionnaire, and satisfaction questionnaire. Descriptive statistics used for the analysis included frequency, percentage, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 37 publications
0
5
0
7
Order By: Relevance
“…In Thailand, the concept of needs assessments has evolved into the PNI modified (Priority Needs Index) formula [63], which assesses and prioritizes development needs based on various indicators and criteria tailored to Thailand's specific context and requirements [64]. The formula for calculating the outcome of this process was as follows [69]. PNI Modified = (I − D)/D…”
Section: Learner Needs Assessment Resultsmentioning
confidence: 99%
“…In Thailand, the concept of needs assessments has evolved into the PNI modified (Priority Needs Index) formula [63], which assesses and prioritizes development needs based on various indicators and criteria tailored to Thailand's specific context and requirements [64]. The formula for calculating the outcome of this process was as follows [69]. PNI Modified = (I − D)/D…”
Section: Learner Needs Assessment Resultsmentioning
confidence: 99%
“…The descriptive approach is used, and the current research uses the creative cognitive processes scale by Miller (2014) adapted by Marwa Baghdadi (2019). the creative melboip -glovets scale by Khamcharoen, et al(2021) adapted by the researcher, ttf nni creative self-efficacy scale by the researcher, and using correlation coefficients and gradient multiple regression analysis, the study concluded that there is a Statistically significant correlational relationship between creative cognitive processes and creative problem-solving and each of as well as the ideas manipulation, flow, analogical thinking, idea generation, incubation, and mental imagery, with a significant positive contribution rate of (0.793), (0.809), (0.812), (0.817), (0.820), (0.821), respectively in predicting the creative problem-solving، There is also a statistically significant correlation between the creative cognitive processes and the creative self-efficacy of the ideas manipulation, analogical thinking, incubation, flow, idea generation, contributes to a significant positive contribution rate of (0.720), (0.740), (0.749). ), (0.753), (0.757), respectively, in predicting creative self-efficacy and There are direct and total constructive causal effects for the relationships between creative melboip -glovets and creative self-efficacy as dependent variables, and creative cognitive processes as an independent variable.…”
Section: ‫ناهد‬ ‫منير‬ ‫مكاري‬mentioning
confidence: 99%
“…En la actualidad, los educadores están aprovechando los avances tecnológicos para innovar en sus cursos, sea en modalidades presenciales o a distancia (Camps-Ortueta et al, 2023;Colaco y Antao, 2023;Kadioglu-Akbulut et al, 2023;Kosmas y Zaphiris, 2023). Uno de esos recursos son los muros virtuales, los cuales representan una alternativa tecnológica que puede implementarse en cualquier modalidad educativa (Khamcharoen et al, 2022).…”
Section: Introductionunclassified